Assessment of USGS BCR-2 as a reference material for silicate rock u-pa disequilibrium measurements - Prytulak, J; Elliott, T; Hoffmann, D; Coath, C (2008)
The accuracy of 231 Pa- 235 U measurements can be readily assessed using a secular equilibrium reference material (RM), but a secular equilibrium RM is also required to calibrate the 233 Pa spike used in 231 Pa determinations. The only silicate RM commonly accepted to be in secular equilibrium is Table Mountain Latite (TML) and so an additional reference is required. Our measurements on the widely available USGS BCR-2 (Basalt Columbia River) rock powder yielded (231Pa/ 235U) = 0.997 ± 0.013 2s (n = 10), indicating its value as a secondary reference to test the fidelity of U-Pa determinations. Such a reference material additionally provides a useful check on data reduction, which our literature survey highlights can lead to discrepancies of up to 53% between reported (231Pa/ 235U) activity ratios and corresponding U and Pa concentration data. © 2007 International Association of Geoanalysts.